2015
DOI: 10.3233/cbm-140436
|View full text |Cite
|
Sign up to set email alerts
|

Expression and epigenetic regulation of DACT1 and DACT2 in oral squamous cell carcinoma

Abstract: Patients older than 56 years old were about 5 times more likely to have DACT2 promoter hypermethylation. These findings could partially explain why older subjects are more prone to carcinogenesis. Wnt/β-catenin pathway plays an important role in carcinogenesis, and the study of their regulators may help understand malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
3
13
0
5
Order By: Relevance
“…Downregulation or epigenetic silencing of this gene results in dysregulation of these pathways resulting in carcinogenesis. 15 HOXD10 was significantly upregulated in all 3 comparisons in our samples. It has been shown that high expression of HOXD10 gives cancer cells a proliferative and migratory advantage whereas low expression may support invasion and metastasis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Downregulation or epigenetic silencing of this gene results in dysregulation of these pathways resulting in carcinogenesis. 15 HOXD10 was significantly upregulated in all 3 comparisons in our samples. It has been shown that high expression of HOXD10 gives cancer cells a proliferative and migratory advantage whereas low expression may support invasion and metastasis.…”
Section: Discussionmentioning
confidence: 69%
“…DACT2 gene regulates the TGF B pathway and Wnt pathway. Downregulation or epigenetic silencing of this gene results in dysregulation of these pathways resulting in carcinogenesis . HOXD10 was significantly upregulated in all 3 comparisons in our samples.…”
Section: Discussionmentioning
confidence: 73%
“…In addition to deletion, epigenetic modifications of DACT genes were also reported. For instance, DACT1 and DACT2 were reported to be methylated in hepatocellular carcinoma, oral squamous, gastric cancer, nasopharyngeal carcinoma, thyroid cancer, colon cancer and lung cancer (10,(26)(27)(28)(29)(30)(31). In addition, DACT3 was identified to have histone modifications in colorectal cancer (25,26,32).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, decreased expression and promoter hypermethylation of DACT1 and DACT2 have been found in some primary tumors and tumor cell lines, including hepatocellular carcinoma [15], breast cancer [16], lung cancer [17], colorectal cancer [18] and some other cancers. However, Schussel et al [19] showed quite a different result which the promoter methylation of DACT1 and DACT2 may not be a common event in oral squamous cell carcinoma. Although the promoter of DACT3 also has a large CpG Island, but the study in colorectal cancer indicates that the histone modification, rather than the aberrant, may be the main regulated mechanism for inactivation of this gene [18].…”
Section: Introductionmentioning
confidence: 99%